Остаточный ресурс высокотемпературных элементов паровой турбины К-200-130 ЛМЗ - Черноусенко, Ольга Юрьевна (Национальный технический университет "Харьковский политехнический институт", 2009)
The enrichment and analysis of the calculated estimation of leavingal resource of steam turbine К-200-130 №11, 13–15 is offered with calculating heat state (HS), stressed-deformed state (SDS), and little cycle of lassitude of hightemperature elements of CHP and CMP for exploitation modes energy blokes.
Keywords: визуальный контроль; диски ступеней; пусковые режимы; работа дренажей